Efficient dye regeneration at low driving force achieved in triphenylamine dye LEG4 and TEMPO redox mediator based dye-sensitized solar cells1. Issue 24 (28th June 2015) - Yang, Wenxing; Vlachopoulos, Nick; Hao, Yan; Hagfeldt, Anders; Boschloo, Gerrit
<x xml:space="preserve">Abstract</x> Minimizing the driving force required for the regeneration of oxidized dyes using redox mediators in an electrolyte is essential to further improve the open-circuit voltage and efficiency of dye-sensitized solar cells (DSSCs).